Revealing the Multiculturalism of Singapore Literature: Yeng Pway Ngon, Poems 1: Rebellion, Translated by Alvin Pang and Goh Beng Choo - Lay, Tan Chee (SARE: Southeast Asian Review of English, 2017)
REVIEW